2017
DOI: 10.1136/bcr-2017-220678
|View full text |Cite|
|
Sign up to set email alerts
|

Valacyclovir-associated neurotoxicity treated with intensification of peritoneal dialysis

Abstract: We report a 57-year-old woman with end-stage renal disease (ESRD) on maintenance peritoneal dialysis (PD), who presented to the emergency room (ER) by ambulance with complaints of confusion and altered sensorium for 48 hours. She had been reviewed in a walk-in clinic 72 hours earlier and had been prescribed the standard 1000 mg three times per day of valacyclovir for an acute attack of shingles instead of 500 mg once a day on ESRD. In the ER, she received further 500 mg of intravenous acyclovir as herpes encep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…Valacyclovir-associated neurotoxicity usually occurs within 48-72 h of treatment start, and the symptoms can be gradually relieved after the drug is discontinued for 4-14 d (Table 1). For the patient in the present study, the time of onset and duration of symptoms were similar to those reported in literature[14,16-25] (Table 1).…”
Section: Discussionsupporting
confidence: 88%
“…Valacyclovir-associated neurotoxicity usually occurs within 48-72 h of treatment start, and the symptoms can be gradually relieved after the drug is discontinued for 4-14 d (Table 1). For the patient in the present study, the time of onset and duration of symptoms were similar to those reported in literature[14,16-25] (Table 1).…”
Section: Discussionsupporting
confidence: 88%
“…Peritoneal dialysis has also been used to treat acyclovir toxicity and some authors advocate intensification of this modality for better drug removal [23,24]. Shah et al, in a study of a single patient on continuous ambulatory peritoneal dialysis, found a total body clearance of 48.3 mL/min/1.73 m 2 BSA) and a CAPD clearance of 4.3 mL/min.…”
Section: Discussionmentioning
confidence: 99%
“…Less common symptoms are dysarthria, myoclonus, and rhabdomyolysis [5]. These symptoms that have been reported occur in patients on either hemodialysis or PD and typically resolve two to seven days after removing the offending medication [5,6].…”
Section: Discussionmentioning
confidence: 98%
“…Cases of valacyclovir toxicity have typically reported that the toxicity occurs within 24 to 72 hours, and typical neurological symptoms include hallucinations, confusion, lethargy, fear of death, ataxia, and death [4]. Less common symptoms are dysarthria, myoclonus, and rhabdomyolysis [5]. These symptoms that have been reported occur in patients on either hemodialysis or PD and typically resolve two to seven days after removing the offending medication [5,6].…”
Section: Discussionmentioning
confidence: 99%